Cross-frequency coupling of alpha oscillatory power to the entrainment rhythm of a spatially attended input stream - Wilson, Tommy J.; Foxe, John J. (Cognitive neuroscience, 2020)
Neural entrainment and alpha oscillatory power (8-14 Hz) are mechanisms of selective attention. The extent to which these two mechanisms interact, especially in the context of visuospatial attention, is unclear. Here, we show that spatial attention to a delta-frequency, rhythmic visual stimulus in one hemifield results in phase-amplitude coupling between the delta-phase of an entrained frontal source and alpha power generated by ipsilateral visuocortical regions. The driving of ipsilateral alpha power by frontal delta also correlates with task performance. Our analyses suggest that neural entrainment may serve a previously underappreciated role in coordinating macroscale brain networks and that inhibition of processing by alpha power can be coupled to an attended temporal structure. Finally, we note that the observed coupling bolsters one dominant hypothesis of modern cognitive neuroscience, that macroscale brain networks and distributed neural computation are coordinated by oscillatory synchrony and cross-frequency interactions.